The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/rnj.66
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Hygiene Program Implementation in Patients with Traumatic Brain Injury

Abstract: Sleep disorders have a major impact on health outcomes in patients with TBI. To optimize rehabilitation and ultimately improve functional outcomes of patients with TBI, implementation of evidence-based clinical guidelines for sleep is imperative. We report our initial experience with implementation of sleep guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The participants described that sleep disturbances resulted in fatigue and negative emotions, which decreased their motivation to engage in multiple health behaviors. A mixed methods study of sleep habits among patients with traumatic brain injury showed that inadequate sleep had a major impact on health outcomes and reduced adherence to rehabilitation activities (De La Rue-Evans, Nesbitt & Oka, 2013). Future studies of individuals with stroke should examine whether sleep disturbances need to be addressed before multiple behavior changes can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The participants described that sleep disturbances resulted in fatigue and negative emotions, which decreased their motivation to engage in multiple health behaviors. A mixed methods study of sleep habits among patients with traumatic brain injury showed that inadequate sleep had a major impact on health outcomes and reduced adherence to rehabilitation activities (De La Rue-Evans, Nesbitt & Oka, 2013). Future studies of individuals with stroke should examine whether sleep disturbances need to be addressed before multiple behavior changes can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that CBTI reduced daytime fatigue and improved nocturnal sleep quality among patients with TBI [48]. Similarly, a recent sleep health program by the Department of Veteran's Affairs, which incorporated CBTI, relaxation techniques, sleep restriction, stimulus control, and exercise proved beneficial in patients with persistent TBI symptoms [106]. Melatonin may serve a beneficial role in the treatment of mTBI-induced insomnia, but definitive trials are not yet available.…”
Section: Insomnia and Circadian Dysregulationmentioning
confidence: 99%
“…The self-reported symptoms of neck pain, tingling, drowsiness, and nervousness are potentially modifiable in duration throughout the initial 24 hours after an SC. 42 Mittenberg et al 43 reported that early structured education of concussed patients by a therapist, which consisted of techniques for stress reduction and gradual resumption of premorbid activities along with providing a 10-page educational manual, significantly reduced recovery time compared with those who received routine hospital treatment and discharge. The theoretical rationale for this finding is based on the cognitive-behavioral model.…”
Section: Discussionmentioning
confidence: 99%
“…To address drowsiness, a checklist may be given to help educate and remind athletes about proper sleep hygiene. 42 Information about limiting barriers to sleep may reduce drowsiness duration within the initial 24 hours by facilitating sleep the night of the injury.…”
Section: Discussionmentioning
confidence: 99%